The Paradox of Web Service Composition and Load Balancing: Theoretical Compatibility vs. Business Reality - Maksymilian Iwanow (Engineering, MAthematics and Computer Science Journal (EMACS), 2026)
Web services have become a fundamental building block of modern IT infrastructures. They underpin both: internal system integration and the delivery of complex business functionalities – and as organizations continue to shift toward service-oriented or microservice-based architectures, managing service interactions well is no longer an option. Composition and load balancing have grown into critical concerns for any company serious about keeping production systems running reliably at scale. This paper explores where service composition and load balancing conceptually overlap – and, perhaps more interestingly, where they contradict each other. The tension becomes visible when these mechanisms are treated as multi-criteria optimization problems rather than as pragmatic, cost-driven business decisions. To examine this, the study combines a structured literature review with informal participant observation carried out in a real enterprise environment. What emerges from the analysis is that service composition – broadly, the integration of multiple sub-services to fulfill a specific functional goal – frequently runs into load balancing, which distributes incoming requests across service instances to make efficient use of available resources. In practice, though, this intersection tends to be poorly understood. Academic literature and industry practice alike treat both mechanisms inconsistently, often without acknowledging the tensions between them. This paper tries to cut through that ambiguity by combining a close reading of the literature with hands-on professional perspective. The result is a synthesis that places itself somewhere between theory and practice. In spite of definitive answers, the paper is also intended as a starting point for a broader conversation – one that feels overdue, given how many relevant questions remain underexplored.